2018
DOI: 10.1002/tox.22563
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic potential of fenvalerate and triadimefon on endocrine disruption and oxidative stress during rare minnow embryo development

Abstract: Pyrethroids have been reported to interact synergistically when co-exposed with azoles fungicides in different organisms. In the present study, we investigated the mixture toxicity of fenvalerate (FEN) and triadimefon (TDF) toward embryos of Gobiocypris rarus after 96 h exposure. Results demonstrated that TDF enhanced the acute toxicity of FEN. Exposure to binary mixtures of FEN and TDF resulted in synergistic responses of endocrine disruption by inducing the transcripts of several genes including vtg, erα, er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This defense mechanism is activated in the earliest developmental stages of fish ( e.g. , Wu et al 2018). Expression of hsp70 was more than onefold down-regulated 3 hr after acute shock in EPH treated fish (but not in fish of the other treatments) and 3′UTR regions 200 kb up- and down-stream showed increased DNA methylation with EPH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This defense mechanism is activated in the earliest developmental stages of fish ( e.g. , Wu et al 2018). Expression of hsp70 was more than onefold down-regulated 3 hr after acute shock in EPH treated fish (but not in fish of the other treatments) and 3′UTR regions 200 kb up- and down-stream showed increased DNA methylation with EPH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the last 20 years of research found that triadimefon can affect species by causing multiple toxic effects on the thyroid, reproduction system, liver, nervous system as well as carcinogenicity and teratogenicity [12,16,20,62]. Furthermore, synergistic effects with other pesticides were also observed [13,63,64]. In this study, effects and mechanisms of action and toxic potencies of triadimefon have been summarized.…”
Section: Effects and Mechanisms Of Toxicity Of Triadimefon To Aquatic Organismsmentioning
confidence: 94%
“…Per uorooctanoic Acid, which can be present in some formulations, signi cantly increased toxic potency of triadimefon [64]. The 96-h exposure of rare minnow to a mixture of fenvalerate (0.288 mg/L) and triadimefon (6.44 mg/L) illustrated that the two chemicals can interact to cause acute toxicity, endocrine disruption, and oxidative stress during rare minnow embryo development at lesser doses [13].…”
Section: Metamorphic Development Was a Predominant Effect Of Triadimefon On Amphibians Triadimefon Canmentioning
confidence: 99%
See 2 more Smart Citations